Fostering Tolerance in Early Childhood in Islamic Perspectives and Social Learning Theory - Ida Windi Wahyuni; Syaifuddin Azwar (Program Studi Pendidikan Islam Anak Usia Dini, UIN Sunan Ampel Surabaya, 2022)
The next generation of the nation not only affects the intellect but can change all aspects of life. Tolerance can occur due to habit and modeling factors. Individuals can do something and the modeling process through direct observation or experience. The purpose of this paper is to examine the development of tolerance in the Islamic perspective and social learning theory. This research is part of a literature study research with a complete series of material from various library sources and is formulated with the results described in detail in depth. The results show that the concept of religious tolerance in children not only allows people to practice their own beliefs, but also opens the possibility of mutually beneficial cooperation in differences in each person. The community environment is heterogeneous. Children from various backgrounds learn together and are tolerant of having a role to create an attitude of mutual respect and appreciation in differences between these children.